2022
DOI: 10.3390/ijms23031086
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle Fusion as a Target Process for the Action of Sphingosine and Its Derived Drugs

Abstract: The fusion of membranes is a central part of the physiological processes involving the intracellular transport and maturation of vesicles and the final release of their contents, such as neurotransmitters and hormones, by exocytosis. Traditionally, in this process, proteins, such SNAREs have been considered the essential components of the fusion molecular machinery, while lipids have been seen as merely structural elements. Nevertheless, sphingosine, an intracellular signalling lipid, greatly increases the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…Others have found that siponimod interacts with the cellular (anti-)oxidant system by, for example, restoring thiol levels and increasing the expression and activity of protective transcription factors [ 31 ]. Moreover, it seems to induce organelle fusion in other models [ 71 ]. We can only speculate why siponimod demonstrated a more pronounced effect on restoring mitochondrial morphology compared to fingolimod in our experiments, despite presumably antagonizing the same S1PR inside the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that siponimod interacts with the cellular (anti-)oxidant system by, for example, restoring thiol levels and increasing the expression and activity of protective transcription factors [ 31 ]. Moreover, it seems to induce organelle fusion in other models [ 71 ]. We can only speculate why siponimod demonstrated a more pronounced effect on restoring mitochondrial morphology compared to fingolimod in our experiments, despite presumably antagonizing the same S1PR inside the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of small sphingolipids also influences cellular exocytosis. Sphingosine, a cationic intracellular signaling lipid, greatly increases the release of neurotransmitters in neuronal and neuroendocrine cells, whilst its zwitterionic analogue, sphingosine-1-phosphate (see Table 1 ) inhibited it at low concentrations [ 61 ]. Phospholipase anionic products, such as PA, PIP 2 and other phosphoinositides as well as phosphatidylserine activates the vesicle exocytosis [ 27 ].…”
Section: Membrane Fusion and Cell Functionmentioning
confidence: 99%
“…This represents an underestimated mechanism of pharmacological action. Other amphiphilic drugs have been reported to act on the efficiency of vesicle fusion [ 61 ]. However, the pharmacological regulation of membrane curvature properties has seldom been approached and represents a new frontier for the design of new therapies.…”
Section: Summary and Perspectivesmentioning
confidence: 99%